Spirituality and spiritual care in palliative care as interpreted by German medical professional societies (Paliativní medicína, 2023)
The paper introduces the treatment of the concepts of spirituality and spiritual care in selected German medical professional societies in the context of palliative care. It first introduces spirituality and spiritual care in palliative care. It then discusses spirituality and spiritual care as presented by the founder of the hospice movement, Cicely Saunders, as well as her concept of spiritual pain. Then the selected German professional societies and their conceptions of the various concepts in the field of spirituality and spiritual care is examined. Finally, the important relationship between spirituality, spiritual care and ethics is highlighted.
Keywords: spirituality, spiritual care, palliative care